DESAIN SISTEM ALARM MOBIL BERBASIS SMS - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
The alarm device is very important in a vehicle, especially on four-wheeled vehicles. Alarm device installed to avoid in case of danger of theft or destruction of the car. So designed car alarm system that can send short message to car owner who use AT89S52 microcontroller. The hardware arrangement of the car alarm system uses the SMS-based AT89S52 microcontroller in this design, consisting of four main parts of the circuit, the minimum system circuit of microcontroller, power supply, serial communication, Input / Output. In SMS text sent from Wavecom M1306B modem and received by mobile (mobile phone) to SMS center or SMS Center flows in form of PDU (Protocol Data Unit). In the sms format is divided into several segments of data that each segment has a specific purpose. The segments are: SMS center number, destination number, bytes for the purpose of setting this SMS and most important is the SMS content that has been changed in the form of a PDU. To be able to send or upload SMS data to the modem and ordered the modem to send SMS data it required AT Command instructions.